‘Per diporto ò devotione’: Curiosità, godimento dei monumenti ed erudizione nella Roma ricercata ... di Fioravante Martinelli (1644) - Parlato, Enrico (Incontri. Rivista europea di studi italiani, 2014)
Curiosities, erudition and the love of monuments in Fioravante Martinelli’s Roma ricercata (1644)This essay discusses the guidebooks to Rome produced in the 1640s by Fioravante Martinelli. These books, explicitly conceived to be used by well-informed foreigners visiting the Eternal City, privilege a perspective which contrary to most conventions frames the city’s heritage in a dominantly christian light, taking not its antique roots but Constantine’s reign as its starting point. Given Martinelli’s pivotal position in the city’s contemporary cultural scene, as a friend of Borromini and being closely linked to the catholic elite, his perspective reveals the ambition to promote this circle’s vision of Rome’s contemporary identity in a corographic context targeting an international audience of intellectuals. This explains why these books adopt on the one hand an unusually small format and the template of realistic itineraries, while on the other hand they offer a most erudite introduction to the monuments to be seen. Since these include many of the fairly recent ambitious building projects by architects like Borromini himself, Martinelli’s guide offers a state-of-the-art introduction to seventeenth-century Rome that because of its documentary value has never lost its appeal.